Kinetic and mechanistic investigations of the Baylis-Hillman reaction in ionic liquids - Singh, Anshu; Kumar, Anil (RSC Advances, 2015)
We report here a quantitative study of the kinetics and mechanism of the Baylis-Hillman reaction in the presence of ionic liquids as solvent media. Apparently, a simple Baylis-Hillman reaction can occur by two different exclusive mechanisms in ionic liquids. The delicate balance of these mechanisms is maintained by the ionic environment employed. The main features of the possible mechanism have been described here along with interesting kinetic consequences. The measurement of rate constants and activation energy parameters demonstrate that as the medium becomes basic, the order of the reaction changes from 1 to 2. An unexpected change in the mechanism of the reaction is observed with a change in the nature of the ionic liquid. The Linear Solvation Energy Relationship has also been used as an investigating tool to delineate the respective contributions of the cation and anion of the ionic liquid. The observation strongly dictates the dependency of the mechanism of the Baylis-Hillman reaction on the nature of the anion of the ionic liquids undertaken for this study.